Implementation of Green Communication in the Front Office Department at New Sunari Lovina Beach Resort - Ni Kadek Dwi Candra; Nyoman Dini Andiani; Putu Indah Rahmawati (International Journal of Green Tourism Research and Applications, 2024)
Green communication is one of the crucial things in realizing an environmentally friendly concept in the hotel industry because the environmentally friendly concept is not only about the natural environment but also how humans communicate well and effectively to start ecologically friendly programs. This research explores the application of green communication. It was carried out by front office staff at New Sunari Lovina Bali Resort, which aims to make communication more effective in transmitting the work obtained and to impact how employees view environmentally friendly management. Data was collected through interviews, observation, and document analysis using descriptive qualitative research methods. These findings show that New Sunari Lovina Beach Resort has implemented green actions, starting with cooperation, coordination, communication, comfort, and problem-solving. Though, implementing green communication at the front office of New Sunari Lovina Bali Resort also faces several obstacles. Lack of staff awareness of sustainable principles, lack of clarity regarding concrete benefits, and operational constraints such as the availability of resources and technology are challenges that must be overcome. The results of this study provide an essential basis for developing effective, sustainable communication strategies in dealing with environmental issues.